Implementation Of Problem Based Learning Models In Learning Systems Of Linear Equations Three Variables - Titania Budiman; Victor R. Sulangi; John R. Wenas (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study investigates whether the use of the Problem-Based Learning model on the Three Variable Linear Equation System increases student learning outcomes. This investigation is quasi-experimental "Quasi Experimental Design". Class X-A as an experimental class with 17 students and X-B as a control class with 17 students at SMA Negeri 2 Tondano in the odd semester of the academic year 2022/2023 comprised the study's sample. An evaluation about the material description of a three-variable system of linear equations served as the research instrument. A pretest and a posttest are used to capture data from the experimental and control groups, respectively. Using the t-test statistic to test the null hypothesis, we obtain tcount = 12.64 and ttable = 2.037 at a significance level of 0.05, thus rejecting H0. The Problem-Based Learning model improved student learning outcomes, according to the study's findings.